KUALITAS PAPAN PARTIKEL DARI CAMPURAN BATANG SORGUM (Sorghum bicolor L.) DAN KAYU AKASIA (Acacia mangium W.) BERDASARKAN KONSENTRASI PEREKAT UREA FORMALDEHIDA - Jamaluddin, . (JURNAL HUTAN LESTARI, 2018)
This research aims to analyze the effect of composition in the mixture of sorghum and acacia wood and the adhesive concentration on particle board quality as well as to determine the material composition and adhesive concentration optimum resulting in particleboard that meet the JIS A 5908 type 8 standard. The composition of sorghum and acacia wood used are 100%: 0%, 50% : 50%, 0% : 100%, and urea formaldehyde adhesives used with concentrations of 8%, 10%, 12%. The particle board is made with a size of 30 cm x 30 cm x 1 cm with a target density of 0.8 gr/cm3  then hot press using temperatures of 1300C with pressure 25 kg/cm2 for 10 minutes. Testing of physical properties (density, moisture content, thickness swelling and water absorption) and mechanical properties (modulus of elasticity, modulus of rupture, internal bond and screw holding strength) were carried out according to JIS A 5908-2003 type 8 standard. The results show that  all treatment fulfill the JIS A 5908-2003 type 8 standard for density, moisture content, modulus of rupture, internal bond and screw holding strength. Whereas, the treatment that meet the JIS A 5908-2003 type 8 standard on modulus of elasticity were adhesive concentration of 8% and composition of 0% : 100%;  adhesive concentration of 10% and composition of 50% : 50%; adhesive concentration of 10% and composition of 0% : 100%; adhesive concentration of 12% and composition of 50% : 50%; adhesive concentration of 12% and composition of  0% : 100%.  The thickness swelling and water absorption were not meet the JIS A 5908-2003 type 8 standard. Particleboard with the composition of sorghum of 50% : acacia of 50% and adhesive concentration of 10% is the optimum treatment that produced the board meet the JIS A5908-2003 type 8 standard.Keywords: acacia wood, baggase sorghum , particle board, physical and mechanical properties